1992
DOI: 10.1139/f92-012
|View full text |Cite
|
Sign up to set email alerts
|

Circannual Cycle of Seawater Adaptability in Oncorhynchus nerka: Genetic Differences between Sympatric Sockeye Salmon and Kokanee

Abstract: 1992. Circannual cycle of seawater c3daptability in Oncorhynchus nerka: genetic differences between syrnpatric sockeye salmon and kokanee. Can. J. Fish. Aquat. Sci. 49: 99-109.Anadromous sockeye salmon and nonanadromous kokanee (Oncorhynchus nerka) spawn syrnpatrically in locc3-tions across British Columbia, yet remain genetically distinct. To investigate the possibility that these differences are maintained by selection against hybrids of the two forms owing to differences in seawater adaptability, we raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…In fact, salinity tolerance improves with size in all salmonids (McCormick and Saunders, 1987 ). Development of salinity tolerance, independent of Parr-smolt transformation, exists naturally in non-anadromous salmonids, such as Salvelinus fontinalis (McCormick et al, 1985 ), and can be stimulated by seawater transfer in landlocked forms, such as kokanee salmon, Oncorhynchus nerka (Foote et al, 1992), and resident brown trout (Quillet et al, 1986; this study).…”
Section: Discussionmentioning
confidence: 76%
“…In fact, salinity tolerance improves with size in all salmonids (McCormick and Saunders, 1987 ). Development of salinity tolerance, independent of Parr-smolt transformation, exists naturally in non-anadromous salmonids, such as Salvelinus fontinalis (McCormick et al, 1985 ), and can be stimulated by seawater transfer in landlocked forms, such as kokanee salmon, Oncorhynchus nerka (Foote et al, 1992), and resident brown trout (Quillet et al, 1986; this study).…”
Section: Discussionmentioning
confidence: 76%
“…Generally, organisms have various biological rhythms (e.g., circadian, circalunar, circatidal, and circannual rhythms) for reproduction, migration, and feeding (Baggerman, 1985;Boujard and Leatherland, 1992;Foote et al, 1992;Gwinner, 1986Gwinner, , 1996Heilman and Spieler, 1999;Mizushima et al, 2000;Satoh et al, 2008;Wikelski et al, 2009;Takemura et al, 2010). Seasonal feeding rhythms usually involve a fasting period; such a pattern has been identified in various organisms, especially in avian and mammalian species (Hissa, 1997;Piersma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The inheritance of nonmigratory and migratory lifehistory types and associated traits has been examined in several salmonid species (Refstie et al 1977;Clarke et al 1992Clarke et al , 1994Foote et al 1992;Johnsson et al 1994;Thrower et al 2004;Duston et al 2005). Although plasticity exists within and across populations (Quinn and Myers 2004;McPhee et al 2007), inheritance studies suggest that both timing of and propensity for smoltification are also under genetic control.…”
mentioning
confidence: 99%
“…In crosses between life-history variants of Chinook salmon that differ in smoltification timing, Clarke et al (1994) found that early smolting (smolting during the first year of life, also called ''ocean type'') was dominant and apparently controlled by few genetic loci; the authors used body morphology and coloration to discriminate between dark, stream-dwelling individuals and silvery, premigratory smolts to determine if Chinook salmon in their study were smolting in their first or second year of life. In species for which both freshwater resident and migratory forms exist, studies evaluating smoltification in intercrosses between resident and anadromous forms indicate that there is also a genetic basis for the propensity to undergo smoltification (Foote et al 1992;Johnsson et al 1994). In these studies, hybrid progeny were made from crosses between anadromous sockeye salmon and freshwater resident kokanee (O. nerka) (Foote et al 1992) and between anadromous steelhead and freshwater resident rainbow trout (O. mykiss) (Johnsson et al 1994); in both studies, hybrids were intermediate between freshwater and migratory forms in their ability to hypo-osmoregulate in seawater, suggesting that propensity for smoltification is under additive rather than dominant genetic control in these species.…”
mentioning
confidence: 99%
See 1 more Smart Citation